Perancangan Media Edukasi Tradisi Pernikahan Adat Tionghoa di Kota Medan - Jessica Prasetio; Rizka Alya Triztika; Elis Savitri (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Rapid technological advancement and globalization have significantly influenced many aspects of society, including the preservation of cultural traditions. Among the Chinese community, particularly the younger generation, knowledge and understanding of traditional Chinese wedding customs have gradually declined. Most young people are familiar only with the general concept of Chinese weddings, while lacking awareness of the ceremonial stages and the cultural meanings embedded in each ritual. The growing influence of foreign cultures, changing lifestyles, and the limited availability of engaging educational resources have further contributed to the fading appreciation of these traditions. This study aims to design an educational medium that introduces the traditional Chinese wedding customs practiced in Medan City and promotes greater awareness of their cultural significance. The design process adopts the Design Thinking approach, which includes the stages of empathize, define, ideate, prototype, and test to ensure that the educational media effectively meets users’ needs. The resulting media utilizes illustrations and visual storytelling to explain each stage of the wedding ceremony in an attractive and easily understandable manner. By presenting cultural information through engaging visual communication, the educational media is expected to improve public knowledge, strengthen cultural appreciation among younger generations, and contribute to the preservation of traditional Chinese wedding customs as an important cultural heritage with enduring historical and philosophical values.